Exploring and expanding the natural chemical space of bacterial diterpenes - Xiuting Wei; Wenbo Ning; Caitlin A. McCadden; Tyler A. Alsup; Zining Li; Diana P. Łomowska-Keehner; Jordan Nafie; Tracy Qu; Melvin Osei Opoku; Glen R. Gillia; Baofu Xu; Daniel G. Icenhour; et al. (Nature Communications)
Abstract Terpenoids are the largest family of natural products but relatively rare in bacteria. Genome mining reveals widespread prevalence of terpene synthases, the enzymes responsible for constructing the hydrocarbon skeletons, in bacteria. Here, we show that 125 (37%) of 334 terpene synthases from 8 phyla, 17 classes, and 83 genera of bacteria are active as diterpene synthases. Isolation and structural elucidation of 28 diterpenes from 31 terpene synthases reveal three previously unreported terpene skeletons, skeletons of natural products from other organisms with unknown biosynthetic pathways, diterpenes that are known in other organisms but to the best of our knowledge not previously seen in bacteria, or new structural and stereochemical isomers of diterpenes. We also identify type I diterpene synthases from myxobacteria and cyanobacteria. This study will help to discover new natural products, advance studies in terpenoid biosynthesis and enzymology, and provide model systems to probe the ecological roles of terpenes.